Positive and negative sides of divorce as refected in anglo-american anti-proverbs - Litovkina, A.T. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
In the present study I am going to explore the positive and negative sides of divorce as it is viewed and conceptualized in the body of Anglo-American anti-proverbs(i.e., deliberate proverb innovations, also known as alterations, parodies, transformations, variations, wisecracks, mutations, or fractured proverbs). My discussion is organized in two sections. While the first one very briefly demonstrates the background of antiproverb research and terminology, the second section treats the advantages and disadvantages of divorce. While the focus of thefirst part of second section is on positive sides of divorce, the second part of it addresses its negative sides. The anti-proverbs discussed in the present study were taken primarily from American and British written sources. The texts of anti-proverbs were drawn from hundreds of books and articles on puns, one-liners, toasts, wisecracks, quotations, aphorisms, maxims, quips, epigrams, and graffiti collected in two dictionaries of anti-proverbs compiled by Anna T. Litovkina and Wolfgang Mieder.
Ағылшын-америкалық мақал-мəтелдерде ажырасудың оң жəне теріс жақтары
Позитивные и негативные стороны развода в англо-американских анти-пословицах
Keywords: anti-proverb; anglo-american; marriage; english; american; divorce; husband; wife; positive; negative